Non-equilibrium potentiometric sensors integrated with metal modified paper-based microfluidic solution sampling substrates for determination of heavy metals in complex environmental samples - Silva, Rochelle (2022)
Metal modified paper-based substrates were utilized for microfluidic paper-based solution sampling coupled with Pb2+-ion selective electrodes (ISEs) with the aim of controlling the super-Nernstian response which usually occurs when using unmodified paper substrates. Potentiometric responses of Pb2+-ISEs coupled with gold, platinum and palladium coated paper substrates were investigated. Potentiometric response time was found to be predominantly dependent on the thickness of metallic layer deposited at the paper substrates. Paper-based substrates coated on both sides with 38 nm gold layers were found to be the most advantageous in controlling the super-Nernstian response of ISEs at non-equilibrium conditions. Durability studies indicated that the lifetime of Pb2+-ISEs could be doubled when used with paper-based substrates in complex environmental samples with high solid-to-liquid content. Determination of lead in real samples using metal modified paper substrates coupled with Pb2+-ISEs was validated by inductively coupled plasma optical emission spectrometry (ICP-OES). Detailed life cycle assessments were performed for model screen printed potentiometric sensors with and without metal modified paper-based solution sampling substrates. The results confirmed that the use of modified paper substrates demonstrated lower environmental impact per potentiometric measurement of Pb2+-ISE in prepared simulated environmental sample as compared to sensors without the use of paper substrates.